Comparison between faculty and students perspectives on the qualities of a good medical teacher: A cross-sectional study - Al-Mohaimeed, Abdulrahman A. (International Journal of Health Sciences, 2018)
Objectives: This study aimed to explore faculty and students` perceptions on the qualities of good medical teachers, and to determine whether the opinions of faculty and students differed. Methods: Two quantitative surveys were performed at Qassim University College of Medicine (QUCOM) using a pre-tested self-administered questionnaire distributed to the faculty and students of the college. It captured their opinions about qualities and attributes of good teachers. Each item was measured on a 5-point Likert scale. Data were entered and analyzed using SPSS. Results: A total of 90 faculty and 356 students responded with a response rate of 64%. Overall scores on the performance and personality scales were similar between faculty and students. Faculty and students agreed that "Organizes good lectures / use of audiovisual aids" and " Expert on the subject /knowledgeable" are important attributes and that telling jokes and the sense of humor or sharing personal experiences are not as important. Students felt it is important for an educator to be respectful, good planner and examiner, whereas faculty members felt that communication skills are of high importance. Conclusion: Faculty development programs should be designed in order to help faculty develop and improve upon the identified qualities.